Fungsi Dinas Pariwisata dalam Pengelolaan Wisata di Kecamatan Sambi Rampas - Yosef Franklin Estrada; Josef Mario Monteiro; Marlyani Anita Seran (Pusat Riset dan Inovasi Nasional, 2025)
Tourism is one of the strategic fields to obtain foreign exchange and support national and regional development. Indonesia has a rich diversity of tourist destinations, spread across the country. One of the regions famous for its beautiful and attractive tourist destinations is East Manggarai Regency, East Nusa Tenggara Province (NTT). This regency has various tourist destinations that attract attention and have unique characteristics. Currently, the focus of the community, particularly the people of East Manggarai Regency, is on the Watu Pajung Beach and Rana Tonjong Lake tourist destinations in Nanga Mbaur and Nanga Mbaling villages, Sambi Rampas sub-district. Considering its potential to increase regional income, this destination is specifically regulated through the East Manggarai Regency Regional Regulation Number 7 of 2016 concerning the management of the Watu Pajung Beach and Rana Tonjong Lake tourism area.This research uses empirical juridical methods, collecting data through interviews, observations, and literature studies. The results of the study show that the implementation of the function of the East Manggarai Regency Tourism Office has shown an increase, but it is not yet optimal. Based on field experience and information obtained, the researcher can provide suggestions and input, namely: The Tourism Office must be more serious in overcoming the obstacles of managing the Watu Pajung Beach and Rana Tonjong Lake tourism to achieve optimal results, and the Local Government supports with larger budget assistance so that the management of tourist destinations is smoother.